2015
DOI: 10.1016/j.jaci.2014.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker-based asthma phenotypes of corticosteroid response

Abstract: Background Asthma is a heterogeneous disease with different phenotypes. Inhaled corticosteroid (ICS) therapy is a mainstay of treatment for asthma but the clinical response to ICS is variable. Objective We hypothesized that a panel of inflammatory biomarkers i.e. FENO, sputum eosinophils and urinary BromoTyrosine (BrTyr) might predict steroid responsiveness. Methods The original study, from which this analysis originates, comprised 2 phases: a steroid naïve phase 1 and a 28-day trial of ICS (phase 2) durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
87
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(97 citation statements)
references
References 42 publications
5
87
1
4
Order By: Relevance
“…Discordance between different biomarkers for airway eosinophilia has been reported previously [17,29]. More interestingly, discordance between various biomarkers of the effects of anti-inflammatory therapy or ability to predict asthma attacks have also been noted [7,29,30]. These data suggest that discordance between biomarkers in different asthma phenotypes may point towards different underlying mechanisms.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Discordance between different biomarkers for airway eosinophilia has been reported previously [17,29]. More interestingly, discordance between various biomarkers of the effects of anti-inflammatory therapy or ability to predict asthma attacks have also been noted [7,29,30]. These data suggest that discordance between biomarkers in different asthma phenotypes may point towards different underlying mechanisms.…”
Section: Discussionmentioning
confidence: 67%
“…In our study, total IgE was relatively more accurate in predicting sputum eosinophilia in nonobese patients compared to obese patients, but had lower diagnostic accuracy than the other two biomarkers. Discordance between different biomarkers for airway eosinophilia has been reported previously [17,29]. More interestingly, discordance between various biomarkers of the effects of anti-inflammatory therapy or ability to predict asthma attacks have also been noted [7,29,30].…”
Section: Discussionmentioning
confidence: 86%
“…264 This is problematic, not least due to the cumbersome nature of inflammatory and 265 challenge measurements that are difficult to perform in a community setting; 266 albeit measuring blood eosinophils might be part of the solution 16 . Cowan et al 267 have suggested using a panel of inflammatory biomarkers to better enable 268 prediction of ICS responsiveness in asthma 46 , but delivery of such a test remains 269 the most difficult hurdle. Even simply using the asthma control questionnaire 24 270 itself seems to be a good predictor of future risk 8 .…”
mentioning
confidence: 99%
“…Serum periostin was identified as a secreted product of IL-13-stimulated bronchial epithelial cells 54 , and has been closely correlated with airway eosinophilia in some 55 , but not all 56,57 , studies. Some 58,59 , but not all 57 , studies suggest a combination of biomarkers gives better prediction of clinical outcomes. Since blood eosinophils are easily accessible, show the best association with airway eosinophilia, and are predictive of treatment response, this biomarker shows great promise for the identification of the eosinophilic endotype in clinical practice.…”
Section: Barcelona Respiratory Networkmentioning
confidence: 99%